Қазақстан Республикасындағы атқару билік органдарының бюджеттік құқықтары: қалыптасуы мен жүзеге асырылуының кейбір теоретикалық сұрақтары - Бейсембеков, А.С. (ҚарМУ басп, 2010)
также правовые механизмы участия данных органов в бюджетном процессе. Автором исследуются структурные подразделения органами исполнительной власти, отвечающие в пределах своих компетенций за реализацию бюджетной политики в стране. Проанализированы на основе соответствующих нормативно-правовых актов полномочия Министерства финансов как структурного подразделения Правительства Республики Казахстан. Исследована тенденция формирования бюджетных прав органов исполнительной власти. In given article are considered questions to realization organ executive authorities of the budgetary rights, as well as legal mechanisms of the participation data organ in budgetary process. Also in article are researched structured subdivisions organ executive authorities, answering within their own competency for realization budgetary politicians in country. They are Analysed on base corresponding to normative-legal acts of the authority Ministry of finance Republics Kazakhstan as structured subdivision Government Republics Kazakhstan. The Explored trend of the shaping the budgetary rights organ исполнительной authorities.